Effect of bio fuel on performance and emissions of spark ignition and compression ignition engines by running on a variety of bio-fuels - Zulhazmi, Ammar Naim; Azlan, Adi Maisur Aflah; Khalid, Amir; Mustaffa, Norrizal; Sulaiman, Syabillah; Razali, Azahari (Penerbit UTHM, 2020)
Internal combustion engines are expected to continue to dominate as the major power source for automotive propulsion in the short to medium term in either major operating mode: spark ignition or compression ignition. An alternative way is needed in order to control the used of gasoline and diesel in a large quantity for a long period of time. An experimental investigation in this review paper was conducted to investigate the effect of bio fuel on performance and emissions of spark ignition and compression ignition engines by running on a variety of bio-fuels, including simulated bio-gas and commercial seed oil. Ricardo E6 variable-compression ratio research engine and dynamo meter fitted with a computer-based cylinder pressure display and processing system were used to run the bio-gas test in spark ignition engine. Single-cylinder direct-injection Gardner (IL2) research engine was used for seed oil bio-fuel test in compression ignition engine. The amount of carbon dioxide (CO2), nitrogen oxide (NOx) and emission for both engine ignitions were referred in this experiment. Besides, the performance for both ignition engines were referred as well. Compression–ignition engine operation with seed-oil derived bio-fuels leads to higher specific fuel consumption but not notably higher emissions of oxides of nitrogen or smoke, when compared with diesel fuel. Specific fuel consumption is lower comparable with spark-ignition engine operation with biogas and specific NOx emissions. Bio fuel is the best material to be used as the replacement for the petroleum such as diesel fuel and petrol fuel because the result shows that bio fuel gives the same performance for engine but with lower pollutants produced thus can reduced the air pollution.